Reconfiguração de redes de distribuição considerando tarifas locacionais dos sistemas de transmissão - Lima, Felipe Nicoletti (2020)
The reconfiguration of distribution networks has been addressed in numerous scientific studies, developing or improving algorithms, using efficient techniques to deal with the problem, seeking mainly to mitigate: the loss of electricity in the distribution systems, the service voltage levels, not neglecting capacity of the feeder circuits. Despite advances in research, there are no references that deal with the subject globally, that is, that consider other factors that fall short of distribution systems. C ontributing to the evolution in the studies of distribution reconfiguration, from a new perspective, th is work seeks to address the classic problem of reconfiguration in the face of the optimization of the loading of distribution substations considering th e location al tariffs of the transmission system, and for that, it was developed a heuristic algorithm. The effectiveness of the distribution reconfiguration algorithm was confirmed through two test systems, the IEEE 33 and 69 nodes , where in both systems t he algorithm proved to be efficient, since it presented satisfactory results, mitigating the costs related to losses of energy, improving voltage levels throughout the network and respecting the maximum current capacity in the feeder circuits. The differen tial of this work is the consideration of aspects of the transmission system in the reconfiguration problem, and the proposed methodology is evaluated from the integrated modeling of the 54 nodes distribution test system to a 4 bus transmission system. The systems are modeled with the aid of the OpenDSS software to determine the power flow, and the network reconfiguration and transmission cost allocation algorithms were developed in a Matlab environment. To enable the analysis of the impact of any investments to marginally increase the capacity of the transmission system and the respective repercussions on the problem of reconfiguration of the distribution system, different scenarios of trans mission line capacity were created, presenting sufficient results to conclude the notorious efficiency of the algorithm, as it presented very low global costs (distribution / transmission) in three scenarios, showing the sensitivity of the TUSTs in the rec onfiguration problem And when there was not a marginal increase in the capacity of transmission lines, generating no need to expand the transmission , t he classic reconfiguration of distribution was obtained , considering only the minimization of energy los s costs and the operation and maintenance costs. In the presented context, the methodology assist s in the optimization of the existing structure, avoiding unnecessary investments both in the transmission and distribution system s , and thereby minimizing dir ectly impacts on the final consumer tariff.